2020
DOI: 10.47162/rjme.61.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptors in normal and acromegalic somatotroph cells: the U-turn of the clinician to immunohistochemistry report – a review

Abstract: This is a narrative review of literature introducing somatostatin receptors (SSTRs) as part of understanding the somatotroph cells since they are positive in normal cells but also in tumoral cells as seen in somatotropinoma, a growth hormone (GH)-producing neoplasia, which causes acromegaly. They are five subtypes of SSTRs (1 to 5), which are immunohistochemically positive in different proportions in somatotropinomas. SSTR types 2 and 5 are most frequent in GH-secreting adenomas and they are both targeted by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The main difference between the patients group included in this study and the other ones mentioned earlier was that most included patients were partially responsive to fg-SRLs, whereas in Iacovazzo et al study only fg-SRLs resistant patients were evaluated for Pasireotide response [ 38 , 40 ]. All things considered, it can be suggested that routine evaluation for IHC expression of SSTRs may be beneficial to facilitate the switch to “targeted therapy”, by subcategorizing patients into fg-SRLs responsive and resistant, for which Pasireotide could be a reasonable first-line therapy choice [ 41 ]. While the evidence for the predictive role of SSTR-2 in SRLs response appears to be clear, results on SSTR-5 are still contradicting, probably also due to the limited evidence and heterogenous patients’ populations used in different studies [ 20 ].…”
Section: Somatostatin Receptors Type 2 (Sstr-2) and Type 5 (Sstr-5)mentioning
confidence: 99%
“…The main difference between the patients group included in this study and the other ones mentioned earlier was that most included patients were partially responsive to fg-SRLs, whereas in Iacovazzo et al study only fg-SRLs resistant patients were evaluated for Pasireotide response [ 38 , 40 ]. All things considered, it can be suggested that routine evaluation for IHC expression of SSTRs may be beneficial to facilitate the switch to “targeted therapy”, by subcategorizing patients into fg-SRLs responsive and resistant, for which Pasireotide could be a reasonable first-line therapy choice [ 41 ]. While the evidence for the predictive role of SSTR-2 in SRLs response appears to be clear, results on SSTR-5 are still contradicting, probably also due to the limited evidence and heterogenous patients’ populations used in different studies [ 20 ].…”
Section: Somatostatin Receptors Type 2 (Sstr-2) and Type 5 (Sstr-5)mentioning
confidence: 99%